The Effect of Communication and Motivation on Employee Performance CV. Eternal Moon Bienar in East Jakarta - Harsono, Yhonanda; Atunisa, Rifa (Journal Socio Humanities Review, 2021)
This study aims to determine how the influence of communication and motivation on employee performance at CV. Eternal Moon Bienar East Jakarta. The method used in this research is descriptive quantitative method. The sampling technique used is random sampling using a sample of 50 respondents. Data analysis used validity test, reliability test, normality test, non multicollinearity test, non autocorrelation test, non heteroscedasticity test, multiple linear regression test, correlation coefficient test, coefficient of determination and significant test (t and f test). The results of the study can be concluded that communication and motivation have a positive effect on the performance of CV employees. Eternal Moon Bienar. This is evidenced by the simple linear regression coefficient of Communication (X1) and Motivation (X2) on Performance (Y) is Y = 7.579 + 0.189X1 + 0.641X2 with the interpretation of the value of the communication correlation coefficient Adj R 0.408 meaning that the two variables have a moderate level of relationship. While the value of the coefficient of motivation adj r of 0.551 means that the two variables have a moderate level of relationship. The level of significance of the effect of communication on employee performance is significant. This can be seen from the value of T arithmetic > T table ( 5.899 >1,678). Likewise, the level of significance of the influence of motivation on employee performance is significant, this can be seen from the value of t count > t table (7,820 > 1,678). Hypothesis Testing obtained the calculated F value > F table (32,061 > 3,200) so that it can be concluded that H0 is rejected and H3 is accepted. This means that there is a positive and simultaneous influence between communication and motivation on employee performance CV. Eternal Moon Bienar.